A delicate balance : equality, non-discrimination and affirmative action in Namibian constitutional law, as compared to South African and U.S. constitutional law - Cassidy, Elizabeth Ann Kandravy (Stellenbosch : Stellenbosch University, 2012)
Thesis (LLM)--University of Stellenbosch, 2002.